Integration of Technology in Higher Education in Myanmar: A Review of University Teachers’ Perceptions of Barriers and Supports - Khin, Nay Chi (Technium Social Sciences Journal, 2021)
Abstract. Educational reform has been performed with respect to the integration of technology in daily classroom practices at higher education level in Myanmar. Digital technologies and digital classrooms become the most significant and dynamic issues in the education sector. Since Myanmar is a lower level income country at the very early stage of ICT development, many challenges and barriers would be inevitably experienced both by teachers and students. This study aims to examine the perceptions of university teachers to technology integration in classroom practices and possible barriers and supports for creating digital classrooms. With this aim, through the identification of individual, professional, institutional and contextual barriers, this study seeks to reveal the perceptions, barriers and challenges and supports needed for implementing digital classrooms at university level. Online survey was used to collect data. The language used in the survey is English. Two hundred fifty-two university teachers participated in the survey to examine potential barriers and supports to integrate technology in classrooms at higher education level in Myanmar. The data was analysed by using mixed method, involving quantitative analysis method and qualitative analysis method. This paper aims to meet the needs of the educational reform performing at higher educational level in Myanmar.